2001
DOI: 10.1051/0004-6361:20011322
|View full text |Cite
|
Sign up to set email alerts
|

An XMM-Newton study of the X-ray binary MXB 1659-298 and the discovery of narrow X-ray absorption lines

Abstract: Abstract. We report the discovery of narrow X-ray absorption lines from the low-mass X-ray binary MXB 1659-298 during an XMM-Newton observation in 2001 February. The 7.1 hr orbital cycle is clearly evident with narrow X-ray eclipses preceded by intense dipping activity. A sinusoid-like OM B-band modulation with a peak-to-peak modulation of ∼0.5 mag and a minimum coincident with the X-ray eclipse is visible. EPIC and RGS spectra reveal the presence of narrow resonant absorption features identified with O viii 1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
110
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(127 citation statements)
references
References 25 publications
14
110
3
Order By: Relevance
“…This shows that inclination angle is important in determining the strength of these absorption features, which implies that the absorbing material is distributed in a cylindrical, rather than a spherical geometry, around the compact object. The azimuthal symmetry is implied by the lack of any orbital dependence of these features (e.g., Sidoli et al 2001;Boirin & Parmar 2003), apart during dipping, where the absorbing material seems to be less ionized (see below). Thus, the highly ionized material responsible for the absorption lines is likely to be related to the accretion disk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This shows that inclination angle is important in determining the strength of these absorption features, which implies that the absorbing material is distributed in a cylindrical, rather than a spherical geometry, around the compact object. The azimuthal symmetry is implied by the lack of any orbital dependence of these features (e.g., Sidoli et al 2001;Boirin & Parmar 2003), apart during dipping, where the absorbing material seems to be less ionized (see below). Thus, the highly ionized material responsible for the absorption lines is likely to be related to the accretion disk.…”
Section: Discussionmentioning
confidence: 99%
“…10 i inferred assuming the superluminal jets are perpendicular to the disk (Mirabel & Rodriguez 1994 (Sidoli et al 2001), are −5 and −9 eV in the RGS persistent and dipping spectra, respectively.…”
Section: Rgs Spectramentioning
confidence: 96%
“…Taking these values into account, the luminosity, and not the radius, seems to be the critical parameter for the existence of a wind in the classical dipping sources. Indeed, all dipping sources that show ionised absorption for which no significant blueshifts have been detected (Cottam et al 2001;Sidoli et al 2001;Juett & Chakrabarty 2006;Boirin et al 2005;Iaria et al 2007) have a luminosity below the one needed for the wind to overcome gravity in these models (see Table 1 of Díaz Trigo et al 2006), with the possible exception of MXB 1658−298, which has a luminosity close to the critical value. In contrast, X 1624−490, GX 13+1 and IGR J17480-2446 have luminosities of 4.7 × 10 37 , 6-9 × 10 37 and 3.7 × 10 37 erg s −1 , respectively, close to or above the critical luminosity.…”
Section: Photoionised Absorptionmentioning
confidence: 96%
“…high-inclination sources), in which narrow absorption lines and broad iron lines are observed simultaneously (e.g. Sidoli et al 2001;Parmar et al 2002;Boirin et al 2005;Díaz Trigo et al 2009). Boirin et al (2005) and Díaz Trigo et al (2006) found that a highly ionised absorption plasma is ubiquitous for these sources and inferred that such an equatorial plasma must be present in all LMXBs.…”
Section: Broad Iron Line Emissionmentioning
confidence: 99%
“…In particular, Fe xxv (He-like) or Fe xxvi (H-like) 1s-2p resonant absorption lines near 7 keV were reported from several micro-quasars and neutron star LMXBs (e.g., Kubota et al 2007;Sidoli et al 2001) that are almost all viewed close to edge-on, many of them being dippers (see e.g. Table 5 of Boirin et al 2004a).…”
Section: Introductionmentioning
confidence: 99%